COVID-19 Pandemic and Internally Generated Revenues in Local Governments: Nigeria Experience - Augustine, ADEKOYA, A.; Ayodele, AGBETUNDE, L.; Oladipo, AKINRINOLA, O. (International Journal of Applied Economics, Finance and Accounting, 2021)
The impact of COVID-19 pandemic on individuals, businesses, economy and governments has become a focus of attention in recent times by scholars, administrators and policy makers. Many researches have been conducted on COVID-19 with less focus on its impact on Internally Generated Revenues (IGR) in Local Governments (LGs). COVID-19 pandemic has impaired the economies and activities of the informal sector (IS) which form the nucleus of rate/taxpayers in LGs. This affects LGs finances in meeting the infrastructural and social-economics needs of the people at the grassroots level. Therefore, the study examined COVID-19 and its impact on LGs IGR in Nigeria, and how to enhance future IS tax compliance and LGs IGR. The study employed exploratory research design with focus on literatures in the area of LG administration and COVID-19 pandemic, public sector accounting and finance, and Nigeria constitution. Secondary data on IGR of LGs in Lagos state were collected while descriptive statistics was adopted for data analysis. The study concluded that COVID-19 pandemic affects many lives, business, and governments. It impacted negatively on the revenues and finances of LGs. However, Public trust, accountability and transparency are key to realization of revenues, therefore, policy makers at the LGs needs to recognize the importance and role of IS on economic development and IGR potentials by extending palliatives measures. LGs should also computerize their revenues register while economic recovery team should be set up on revenue assurance, and how to tackle post COVID-19 financial capability and tax evasion.